2016
DOI: 10.1177/0954405415573062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grain size of AISI 304 on the machining performances in micro electrical discharge machining

Abstract: The material removal process of micro electrical discharge machining is based on the instantaneous ultra-high temperature generated by a series of repetitive discharge pulses. Due to the size effects, the polycrystal cannot be considered as continuous and homogeneous material when machining is in micron scale, and the effects of material microstructure should not be neglected. In this article, the thermoelectric characteristics of grain and grain boundary are discussed, and the influence of grain size on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…The grain sizes of workpiece materials have significant impact on the characteristics of micro EDM [130]. The MRR for micro-EDM has a direct relationship with the grain size of the machined workpiece because the effective thermal conductivity and local effective melting point of polycrystalline materials vary with grain sizes of these materials since the grain boundary volume fractions change [131]. It is worth emphasizing that the material microstructure of the processed workpiece plays a significant role in the performance of the micro EDM process.…”
Section: General View Of the Edm Methodsmentioning
confidence: 99%
“…The grain sizes of workpiece materials have significant impact on the characteristics of micro EDM [130]. The MRR for micro-EDM has a direct relationship with the grain size of the machined workpiece because the effective thermal conductivity and local effective melting point of polycrystalline materials vary with grain sizes of these materials since the grain boundary volume fractions change [131]. It is worth emphasizing that the material microstructure of the processed workpiece plays a significant role in the performance of the micro EDM process.…”
Section: General View Of the Edm Methodsmentioning
confidence: 99%
“…While the LPBF-3 sample had an average grain size of 12.64 µm, with the increase in laser energy density, the grain size of LPBF-2 and LPBF-1 increased to 20.58 µm and 21.34 µm, respectively (Table 3). Note that the electrical and thermal conductivities of the material, which affect machinability, are altered by the grain size, grain boundary, and grain orientation; thus, the microstructural characteristics of the samples are critical for determining the machining performance [31,[38][39][40][41].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the thermal and electrical conductivity of polycrystal materials were in uenced by the grain boundary density (as well referring grain size) composed of defects and impurities [33].…”
Section: Resultsmentioning
confidence: 99%
“…XRD patterns and SEM microstructure images of wrought and LPBF-IN718 samples are presented in Figure 2 2). Note that the electrical and thermal conductivities of the material, which affect machinability, are altered by the grain size, grain boundary, and grain orientation, thus, microstructural characteristics of the samples are critical for determining the machining performance [29,[33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%